Method for reducing impurities in silk fibroin preparations
By using tangential flow filtration technology and pH exchange method in the purification process of silk fibroin preparations, elemental impurities such as lithium and bromine are removed, solving the problem of incomplete impurity removal in the existing technology and improving the purity and safety of the product. sex.
Patent Information
- Application Number
- CN202380046691.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-28
- Filing Date
- 2023-05-02
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art is difficult to effectively remove impurities, especially elemental impurities such as lithium and bromine, when purifying silk fibroin preparations, resulting in a high residual amount in the final product, affecting the safety and quality of the product.
By using cutting flow filtration (TFF) technology during purification, combining with pH such as pH such as pH and other electrical spots of Silus protein, and the introduction of salt solution or change the pH value in the replacement of feeding to remove the lithium to remove lithium to remove lithium to remove lithium to remove lithium removal And bromine and other elements impurities.
It significantly reduces the residual amounts of lithium and bromine in silk fibroin preparations, improves the purity and safety of the product, and ensures the safety of applications in pharmaceuticals and consumer products.
Smart Images

Figure BDA0005184570280000141 
Figure BDA0005184570280000151 
Figure BDA0005184570280000271
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to U.S. Provisional Application No. 63 / 337,325 filed on May 2, 2022 and U.S. Provisional Application No. 63 / 420,160 filed on October 28, 2022, which are incorporated herein by reference in their entirety. Background Art
[0003] Silk is a naturally occurring polymer. Most silk fibers come from the cocoons of the silk moth (Bombyx mori) and include fibroin and sericin. Fibroin is the fiber material that forms the polymer matrix that is bound together with sericin. In nature, silk is formed from a concentrated solution of these proteins that are extruded through the silkworm's spinneret to produce a highly insoluble fiber.
[0004] Silk fibroin has many properties that make it an attractive candidate for products supplied to a variety of industries. The strength and flexibility of the polymer support the traditional use of silk fibroin in textiles and materials, while the biocompatibility of silk fibroin has recently received more attention for its applications in medicine and agriculture. As the technology for producing and processing silk fibroin advances, additional uses for silk fibroin in applications related to materials science are being explored.
[0005] Although various products and uses related to silk fibroin are being developed, there is still a need for methods of producing and processing silk fibroin and formulations containing processed silk fibroin that can meet the needs. The present disclosure meets these needs by providing methods of producing and processing silk fibroin and formulations of silk fibroin-based products useful in various industries. Summary of the invention
[0006] In one aspect, a method for purifying a silk fibroin preparation comprises: preparing an aqueous solution of silk fibroin having a concentration greater than or equal to 5% w / v silk fibroin from the silk fibroin preparation, wherein the silk fibroin preparation comprises a chaotropic salt; and exchanging the chaotropic salt from the silk fibroin solution at a pH below the isoelectric point of the silk fibroin, wherein the pH is 2 to 5, replacing the chaotropic salt with a buffer comprising 10-300 mM of a second salt, or a combination thereof, to prepare purified silk fibroin. DETAILED DESCRIPTION
[0007] This article describes the method for reducing impurities in silk fibroin preparations, particularly the element impurities introduced in the purification process. In the process of purifying silk fibroin, silk fibroin is prepared by including the method for the standard of this area dissolved in lithium bromide or another kind of chaotropic salt, and the inventor finds that the standard method of tangential flow filtration (TFF) or dialysis using water only in the retentate / alternative feed provides the final material with lithium much higher than bromide, usually 500-3000ppm Li and 20-200ppm Br, Li and Br are standardized relative to the amount of silk fibroin. This is unexpected, because in a thorough TFF or dialysis process, it is expected that Li and Br will be completely or almost completely removed. In addition, because the mass of Br is 11.6 times greater than the mass of lithium, it is expected that the residue of Br will be 11.6 times more than Li, rather than less than 100 times.
[0008] For example, U.S. Pat. No. 9,517,191 and related patents state that silk fibroin preparations have 0 ppm to 500 ppm of "inorganic residues," such as 10 ppm to 300 ppm of lithium bromide residues, "as measured using a high performance liquid chromatography lithium bromide assay." However, although Example 5 describes a TFF process for removing lithium bromide, the specification does not provide any data demonstrating that lithium and bromide are removed to levels of 10 ppm to 300 ppm. Furthermore, the '191 patent does not disclose whether the level of inorganic residues is standardized relative to the amount of silk fibroin in solution, although this is necessary. For example, any solution can be diluted with DI water to reduce the level of residues in solution to less than 300 ppm, but will not show any improved removal or residues compared to the amount of silk. Furthermore, as shown in the examples herein, repeating the examples of the '191 patent provides silk fibroin materials having 1000-2000 ppm Li and 40-100 ppm Br, with the Li and Br standardized relative to the amount of silk fibroin. The '191 patent does not provide the pH or salt composition of the TFF solution claimed to be used to remove Li and Br residues.
[0009] The inventors unexpectedly discovered that the use of a retentate having a pH of 3 to 4.5, such as a pH of 4, and / or the use of a TFF alternative feed solution having a salt concentration of 10 to 300 mM NaCl, for example, resulted in a dramatic reduction in Li levels, particularly 20-500 ppm standardized relative to the amount of silk fibroin. The Br levels in these same samples can be 200-1500 ppm standardized relative to the amount of silk fibroin. For example, the reduction in Li levels is particularly important for product safety in pharmaceuticals and consumer products. If one wants to maintain a safe level of Li in a pharmaceutical product consisting of dried or concentrated silk fibroin in order to take advantage of the benefits of a large amount of silk, these methods can be employed to ensure more complete removal of elemental impurities.
[0010] In one aspect, a method for purifying a silk fibroin preparation comprises: preparing an aqueous solution of silk fibroin having a concentration greater than or equal to 5% w / v silk fibroin from the silk fibroin preparation, wherein the silk fibroin preparation comprises a chaotropic salt; and exchanging the chaotropic salt from the silk fibroin solution at a pH below the isoelectric point of the silk fibroin, wherein the pH is 2-5, replacing the chaotropic salt with a buffer comprising 10-300 mM of a second salt, or a combination thereof, to prepare purified silk fibroin.
[0011] Raw silk material can be obtained from the silkworm Bombyx mori species. Other examples of silk-producing species include, but are not limited to, Bombyx mandarina, Bombyx sinesis, Anaphe moloneyi, Anaphe panda, Anaphe reticulate, Anaphe ambrizia, Anaphe carteri, Anaphe venata, Anapha infracta, Antheraea assamensis, Antheraea assama, Antheraea mylitta, Antheraea pernyi, Antheraea yamamai, Antheraea polyphemus, Antheraea oculea, Anisota senatoria), Apis mellifera, Araneus diadematus, Araneus cavaticus, Automerisio, Atticus atlas, Copaxa multifenestrata, Coscinocera hercules, Callosamia promethea, Eupackardia calleta, Eurprosthenops australis, Gonometa postica, Gonometa rufobrunnea, Hyalophora acecropia, Hyalophora euryalus, Hyalophora gloveri, Miranda auretia, Madagascar golden orb spider (Nephilamadagascarensis), stick golden orb spider (Nephila clavipes), stick golden orb spider (Pachypasa otus), Artes leaf moth (Pachypasa atus), ricin silkworm (Philosamia ricini), Pinnasquamosa), Rothschildia hesperis, Rothschildia lebeau, SamiaCynthia and Samia ricini.
[0012] In one aspect, the silk fibroin preparation comprises a chaotropic salt. As used herein, a chaotropic salt is a salt that disrupts the structure of macromolecules such as silk fibroin.
[0013] In one aspect, the method comprises preparing an aqueous silk fibroin solution having a concentration greater than or equal to 5% w / v silk fibroin from a silk fibroin preparation, wherein the silk fibroin preparation is prepared by a process comprising dissolving silk fibroin fibers in 5M to 13M LiBr.
[0014] In one aspect, silk fibroin is produced by providing raw silk (e.g., unpurified silk, such as silk thread, cocoon), which includes fibers containing silk fibroin and sericin. First, at a temperature of about 60 to about 90° C., the raw silk is degummed in a salt solution (especially a sodium carbonate solution, whose sodium carbonate concentration is 0.05 to 1M, especially 0.1 to 1M, more especially 0.2 to 0.5M sodium carbonate) for a time of greater than 60 minutes to about 480 minutes. In a preferred aspect, at 85° C., degumming is performed in 0.5M sodium carbonate for 240 or 360 minutes. In one aspect, degumming provides a degummed silk fiber with a sericin concentration of 0-0.5wt%.
[0015] Of particular relevance to the present application is that most prior art methods for purifying silk fibroin use 0.02M sodium carbonate, boiled for 30 or 60 minutes to provide degummed silk fibroin. The inventors have found that the material produced by this prior art method is not conducive to subsequent processing steps, especially TFF performed with silk fibroin fibers at a concentration of 5-20% w / v. The silk fibroin provided by the prior art degumming process is very viscous in solution and cannot be run through TFF at a concentration higher than about 1% w / v. Without being bound by theory, it is believed that the molecular weight, polydispersity and / or molecular weight distribution of the silk fibroin produced by the prior art degumming process are not conducive to subsequent processing steps.
[0016] After degumming, the silk fibroin fiber is further processed by dissolving, preferably dissolved in an aqueous solution comprising a chaotropic agent. Exemplary chaotropic agents include lithium bromide, lithium chloride, calcium chloride, ethanol, guanidine chloride and urea. Dissolving preferably includes dissolving 1 hour to overnight using 5M to 13M lithium bromide at 50°C to 100°C to provide dissolved silk fibers, or using a mixture of calcium chloride, ethanol and water with a molar ratio of 1:2:8 to dissolve the degummed silk fibers at 50°C to 100°C for 1 hour to overnight to provide dissolved silk fibers. In a specific aspect, 10wt% to 20wt% of the silk fibroin is dissolved in 9.3M lithium bromide for 16 hours (overnight) at 80°C. In one aspect, using TFF / dialysis methods as described herein, the purified silk fibroin preparation includes 10 to 600ppm of lithium / mg silk. On the other hand, the purified silk fibroin preparation includes 10 to 600ppm of bromine / the mass of silk fibroin.
[0017] In another aspect, a silk fibroin preparation is prepared by a process comprising dissolving degummed silk fibers using a mixture of calcium chloride, ethanol, and water in a molar ratio of 1:2:8 at 50°C to 100°C for 1 hour to overnight.
[0018] After the silk fibroin fiber is dissolved, it can be diluted and then further purified. On the one hand, the dissolved silk fiber is diluted in water to provide a concentration of 5-20% w / v silk fibroin fiber. Optionally, the diluted silk fibroin solution is filtered through a polypropylene, polyethersulfone, nylon or cellulose, diatomaceous earth, perlite depth prefilter to remove particles and provide a clarified silk fiber solution.
[0019] The silk fibroin aqueous solution having a concentration greater than or equal to 5% w / v silk fibroin is then purified by exchanging a chaotropic salt from the silk fibroin solution at a pH below the isoelectric point of the silk fibroin, wherein the pH is 2-5, replacing the chaotropic salt with a buffer comprising 10-300 mM of a second salt, or a combination thereof, to prepare purified silk fibroin.
[0020] On the one hand, the diluted silk fibroin fiber is then purified by tangential flow filtration (TFF), for example, continuous diafiltration is performed using tangential flow filtration (TFF). Diafiltration is a fractionation process that washes smaller molecules through a membrane, while leaving larger molecules in the retentate without significantly changing the concentration. Diafiltration can be used to remove salts or exchange buffers. Diafiltration can remove ethanol or other small solvents or additives.
[0021] In continuous diafiltration, the diafiltration solution (water, buffer or saline solution) is added to the sample feed reservoir at the same rate as the filtrate is produced. In this way, the volume in the sample reservoir remains constant, but the small molecules (such as salts) that can freely penetrate through the membrane are washed away in the filtrate (also referred to as permeate). Taking the removal of salt as an example, each additional diafiltration volume (DV; also referred to as dialysis volume (diavolume) in this article) further reduces the salt concentration as salt ions are removed from the filtrate. (The diafiltration volume is the sample volume before the diafiltration solution is added.) Anything that is not filtered out is "retentate". In this case, the retentate includes most of the silk fibroin.
[0022] In the processes described herein, in one method, the pH of a "sample" (also referred to as a retentate) comprising silk fibroin is adjusted down to a pH of 2-5, for example, from its initial pH of 8.5-9.
[0023] In one aspect, the exchange of salt ions from the silk fibroin aqueous solution is performed by continuous diafiltration using tangential flow filtration (TFF) with a 5 kDa to 10 kDa molecular weight cutoff membrane, the process comprising: providing a retentate with a reduced pH, and filtering with a replacement feed of water for at least three diafiltration volumes, wherein the retentate with a reduced pH is a retentate comprising silk fibroin and having a pH of 2 to 5. In one aspect, prior to providing the retentate with a reduced pH, the method comprises filtering with a replacement feed of water for at least 3 diafiltration volumes, preferably at least 5 diafiltration volumes.
[0024] The pH-reduced retentate is a retentate comprising silk fibroin and having a pH of 2 to 5, preferably 3 to 4.5, more preferably 3 to 4, and most preferably 4.
[0025] In another aspect, exchanging salt ions from the aqueous silk fibroin solution is performed by dialysis against a buffer having a pH of 2-5, wherein the pH is maintained at 2-5 during at least a portion of the dialysis process, preferably throughout the dialysis process.
[0026] On the other hand, the exchange of salt ions from the silk fibroin aqueous solution is carried out by continuous diafiltration using tangential flow filtration (TFF) with a 5kDa to 10kDa molecular weight cutoff membrane, the process comprising: filtering with at least three diafiltration volumes of a saline solution replacing the feed, wherein the saline solution replacing the feed comprises 10 to 300mM salt. On the one hand, before providing the saline solution replacing the feed, the method comprises filtering at least 3 diafiltration volumes, preferably at least 5 diafiltration volumes, with water replacing the feed.
[0027] In one aspect, the salt solution replaces the feed (e.g., the second salt) and comprises 10 to 300 mM of a Mg salt, a Ca salt, a K salt, or a Na salt, specifically NaCl or CaCl2, more specifically 150 mM NaCl. The pH of the salt solution replacement is not critical, but is preferably unbuffered, such as pH 6-8.
[0028] In another aspect, exchanging salt ions from the aqueous silk fibroin solution is performed by dialysis in a buffer containing 10 to 300 mM monovalent or divalent salt.
[0029] In another aspect, the method further comprises adjusting the pH of the purified silk fibroin preparation to a pH of 7-9, preferably 8.5-9.
[0030] In the following aspects, the silk fibroin preparation is prepared by a process comprising dissolving degummed silk fibers using a mixture of calcium chloride, ethanol, and water in a molar ratio of 1:2:8 at 50°C to 100°C for 1 hour to overnight.
[0031] In one aspect, exchanging salt ions comprises continuous diafiltration by tangential flow filtration (TFF), dialysis, or a combination thereof. In one aspect, calcium ions are reduced to 10 to 500 ppm.
[0032] In this case, salt ion exchange from the silk fibroin aqueous solution is performed by tangential flow filtration (TFF) with a 5 kDa to 10 kDa molecular weight cutoff membrane, the process comprising: providing a retentate with a reduced pH, and filtering with water instead of the feed for at least three diafiltration volumes, wherein the retentate with a reduced pH is a retentate containing silk fibroin and having a pH of 2 to 5.
[0033] Alternatively, the purification of the silk fibroin solution is performed by dialyzing in a buffer having a pH of 2-5, wherein the pH is maintained at 2-5 during at least a portion of the dialysis process, preferably throughout the dialysis process.
[0034] In another alternative, salt ion exchange from the silk fibroin aqueous solution is performed by continuous diafiltration using tangential flow filtration (TFF) with a 5 kDa to 10 kDa molecular weight cutoff membrane, the process comprising filtering with at least three diafiltration volumes of a salt solution replacing the feed, wherein the salt solution replacing the feed comprises 10 to 300 mM of a monovalent or divalent salt.
[0035] In another alternative, exchange of salt ions from the aqueous silk fibroin solution is performed by dialysis in a buffer containing 10 to 300 mM salt.
[0036] In any of the foregoing aspects, the silk fibroin preparation is prepared by degumming silk threads in 0.05 to 1 M sodium carbonate at a temperature of about 60° C. to about 90° C. for a time period of greater than 60 minutes to about 480 minutes to provide degummed silk fibers having a sericin concentration of 0-0.5 wt %.
[0037] After TFF, the solution can be filtered through about 0.8-2 μm polypropylene, polyethersulfone, nylon or cellulose, diatomaceous earth, perlite depth filter and stored frozen at -80°C or stored at 4°C, preferably with a silk fibroin concentration of 5% to 20% (w / v).
[0038] The silk fibroin prepared by the aforementioned method preferably has a weight average molecular weight less than 90kDa or less than that determined by size exclusion chromatography according to the method used, or less than 20kDa determined by dynamic light scattering. It is worth noting that the molecular weight of the silk fibroin preparation determined depends highly on the method for determining molecular weight. The silk fibroin prepared by the aforementioned method also preferably has a polydispersity less than 1.4 determined by dynamic light scattering.
[0039] The silk fibroin preparations disclosed herein can be used, for example, in therapeutic applications, agricultural applications, and / or materials science applications. The SBP can be used in therapeutic applications, wherein the SBP includes or is combined with one or more of the following: (a) a pharmaceutical composition, (b) an implant, (c) a coating, (d) a food or health supplement, or (e) a device, wherein the pharmaceutical composition, implant, coating, supplement, or device optionally includes one or more of the following: (i) an excipient, and (ii) a therapeutic agent. The agricultural composition comprising silk fibroin can also include fertilizers, nutrients, agricultural products, pesticides, insecticides, herbicides, and antifungal agents, etc. In materials science applications, silk fibroin can be combined with the following: a) adhesives; (b) biomaterials; (c) coatings; (d) conductors; (e) composting agents; (f) cosmetics, (g) emulsifiers; (h) excipients, i) fibers; (j) membranes; (k) filters; (l) foods or additives; (m) insulators; (n) lubricants; (o) diaphragms; (p) metals or metal substitutes; (q) microneedles; (r) nanomaterials; (s) particles; (t) paper additives; (u) plastics or plastic substitutes; (v) polymers; (w) sensors; (x) textiles; and / or (y) thickeners.
[0040] Examples of cosmetics include, but are not limited to, shampoo, conditioner, lotion, foundation, concealer, eye shadow, pressed powder, lipstick, lip gloss, ointment, mascara, gel, spray, eyeliner, liquid, solid, eyebrow tint, eyebrow gel, hair spray, moisturizer, dye, mineral, perfume, cologne, rouge, natural cosmetics, synthetic cosmetics, soap, cleanser, deodorant, face cream, towelette, bath oil, bath salts, body moisturizer, nail polish, hand soap, primer, plumper, balm, contour powder, bronzer, setting spray, and setting powder.
[0041] The term "consumer product" as used herein refers to goods or commodities that the public can purchase. Consumer products may include, but are not limited to, agricultural products, therapeutic products, veterinary products, and household products. Non-limiting examples of consumer products include cleaning supplies, sponges, brushes, cloths, protectors, sealants, adhesives, lubricants, protectants, labels, paints, clothes, insulators, devices, bandages, screens, electronic products, batteries, surfactants, synthetic clothing, laundry beads or tablets, dishwashing beads or tablets, glitter, disposable cups, disposable plates, disposable silverware (e.g., forks, knives, spoons), wet wipes, tires, tennis balls, glitter, cigarette butts, tea bags, and paints.
[0042] The present invention is further illustrated by the following examples.
[0043] Example
[0044] Comparative Example 1: DSC-SC-05-01 processing (degumming and desalting as described in Rockwood et al., Nature Protocols, 6, pp. 1612-1631, 2011)
[0045] Silk fibroin is prepared by degumming silkworm cocoons in sodium carbonate solution, dissolving them in lithium bromide, and purifying by dialysis. First, in order to degumming, 3L DI water and 6.4g sodium carbonate are added to a 4L beaker and stirred until dissolved and uniform (0.02M sodium carbonate). The solution is covered with foil and heated to boiling. 7.5g of cocoons cut into small pieces are added. The cocoons are then degummed for 30 minutes while boiling under periodic stirring. After 30 minutes, the silk is taken out and rinsed under cold running water. Then rinsed with stirring in 1.5L DI water for 20 minutes, exchanged twice (rinsed 3 times in total). The silk is then squeezed until all water is removed, stretched, and placed on foil and dried overnight in a fume hood at room temperature.
[0046] After drying, 5.4g of silk fibroin was loaded into a 100mL beaker and 21.6mL of 9.3M lithium bromide was added. The beaker was covered with foil and heated at 60°C for 4 hours. The resulting 20% (w / v) silk fibroin lithium bromide solution was then poured into a 3.5kDa dialysis cassette and placed in 5L DI water under stirring for dialysis. In the next 48 hours, water was completely exchanged 6 times. After dialysis, the solutions were combined, centrifuged at 10000x g for 20 minutes to remove any insoluble particles, and stored at 4°C before analysis.
[0047] Comparative Example 2: DSC-SC-05-02 Processing (Degumming and Desalting as Described by Rockwood et al.)
[0048] Silk fibroin was prepared using the method of Comparative Example 1, except that degumming was performed by boiling for 60 minutes. Comparative Example 3: DSC-SC-06-01 processing (degumming and desalting were performed as described in US 9,517,191)
[0049] Silk fibroin is prepared by degumming silkworm cocoons in a sodium carbonate solution, dissolving in lithium bromide, and purifying by dialysis. First, 1L DI water and 2.1g sodium carbonate are added to a 2L beaker and stirred until dissolved and uniform (0.02M sodium carbonate). The solution is covered with foil and heated to boiling. 10g of silkworm cocoons cut into small pieces are added. The cocoons are then degummed for 30 minutes while boiling with periodic agitation. After 30 minutes, the silk is immediately removed and placed in 1L DI water heated to 60°C for 20 minutes. It is then removed and rinsed under cold tap water. The silk is then squeezed until all the water is removed, stretched, and placed on foil and dried overnight in a fume hood at room temperature.
[0050] After drying, 7.2g of silk fibroin was loaded into a 100mL beaker and 28.8mL of 9.3M lithium bromide was added. The beaker was covered with foil and heated at 100°C for 1 hour. The resulting 20% (w / v) silk fibroin lithium bromide solution was then poured into a 3.5kDa dialysis cassette and placed in 5L DI water under stirring for dialysis. In the next 48 hours, water was completely exchanged 6 times. After dialysis, the combined solutions were centrifuged at 10000x g for 20 minutes to remove any insoluble particles and stored at 4°C before analysis.
[0051] Comparative Example 4: DSC-SC-06-02 processing (degumming and desalting as described in US 9,517,191)
[0052] Silk fibroin was prepared using the same method as in Comparative Example 3, except that degumming was performed by boiling for 60 minutes.
[0053] Comparative Example 5: DSC-SC-07 processing (degumming similar to WO 2020 / 247594, Example 34; desalting as described in Rockwood et al.)
[0054] Silk fibroin is prepared by degumming silk threads in a sodium carbonate solution, dissolving in lithium bromide, and purifying by dialysis. Silk fibroin is prepared by degumming silk threads in a sodium carbonate solution, dissolving in lithium bromide, and purifying by tangential flow filtration. 31.3L of water and 1.66kg of sodium carbonate (0.5M sodium carbonate) are added to a container and heated to 85°C. 2.5kg of silk threads are added to the solution. The silk threads are degummed at 85°C for 4 hours. After 4 hours, the silk threads are taken out and rinsed under DI water to remove excess carbonate solution. The silk fibroin fibers are then squeezed to remove water and dried in an oven at 60°C for two days.
[0055] After drying, 7.5g silk fibroin was loaded into a 100mL beaker and 30mL 9.3M lithium bromide was added. The beaker was covered with foil and heated overnight (about 20 hours) at 60°C. The resulting 20% (w / v) silk fibroin lithium bromide solution was then poured into a 3.5kDa dialysis cassette and placed in 5L DI water under stirring for dialysis. In the following 48 hours, water was completely exchanged 6 times. After dialysis, the combined solution was centrifuged at 10000x g for 20 minutes to remove any insoluble particles and stored at 4°C before analysis.
[0056] Comparative Example 6: TF-124 processing: (similar to degumming and desalting in Example 34 of WO 2020 / 247594)
[0057] Silk fibroin (SF) was prepared by first degumming silk threads in a sodium carbonate solution. 31.3 L of water and 1.66 kg of sodium carbonate (0.5 M sodium carbonate) were added to a container and heated to 85°C. 2.5 kg of silk threads were added to the solution. The silk threads were degummed at 85°C for 4 hours. After 4 hours, the SF threads were removed and rinsed in DI water to remove excess carbonate solution. The SF fibers were then squeezed to remove water and dried in an oven at 60°C for two days.
[0058] To dissolve the degummed SF fibers, 280 g of degummed SF was placed in a 1-gallon glass jar along with 1.74 kg of 9.3 M lithium bromide solution. The jar was incubated overnight at 60° C. to dissolve the SF fibers. The silk fibroin solution was diluted from 20% (w / v) SF to 5% (w / v) SF with DI water prior to tangential flow filtration. The diluted solution was then filtered through a cellulose membrane of approximately 5 μm to remove any remaining particles.
[0059] Use with Single 1.14m of 5kDa membrane 2 A 3-cassette tangential flow filtration (TFF) system was used to remove lithium bromide. Before introducing SF into the system, the system was washed with DI water and sterilized with 0.1 N sodium hydroxide. The system was then flushed with water to remove the sodium hydroxide.
[0060] Using a TFF system, the solution was concentrated from 5% (w / v) to 10% (w / v) SF. Continuous (or constant volume) diafiltration was performed with 10% (w / v) SF to remove lithium bromide. The silk fibroin and lithium bromide solution was diafiltered for 10 dialysis volumes using DI water as feed. The permeate flux was measured in liters / m per half dialysis volume. 2 Membrane surface area / hour. The solution was then concentrated to half of its diafiltration volume and collected. After TFF, the solution was filtered through an approximately 1 μm cellulose filter and stored at 4°C until elemental analysis was completed.
[0061] Inventive Example 7: TF-122 Processing:
[0062] The SF was first degummed and dissolved as described in Example 6, except that 283 g of degummed SF was placed in a 1-gallon glass jar with 1.82 kg of 9.3 M lithium bromide solution. The TFF system was the same as in Example 6. Continuous diafiltration was performed with 10% (w / v) SF to remove lithium bromide. The silk fibroin was diafiltered for 7 dialysis volumes with an alternative feed of 150 mM sodium chloride aqueous solution. The solution was then concentrated to half of its diafiltration volume and collected. After TFF, the solution was filtered through an approximately 1 μm cellulose filter and stored at 4° C. until elemental analysis was completed.
[0063] Inventive Example 8: TF-123 Processing
[0064] The SF was first degummed and dissolved as described in Example 6, except that 283 g of degummed SF was placed in a 1-gallon glass jar along with 1.82 kg of 9.3 M lithium bromide solution. The TFF system was the same as in Example 6.
[0065] The silk fibroin and lithium bromide solution was first adjusted to pH 4 with hydrochloric acid. Using a TFF system, the solution was concentrated from 5% (w / v) to 10% (w / v) SF while maintaining a pH of 4. Continuous diafiltration was performed at 10% (w / v) SF to remove lithium bromide. The feed diafiltration silk fibroin was replaced with DI water for 7 dialysis volumes while maintaining a pH of 4. The solution was then concentrated to half of its diafiltration volume and collected. The silk fibroin solution was then quickly adjusted to a pH of 8.5 to 9.0 with sodium hydroxide. The solution was filtered through an approximately 1 μm cellulose filter and stored at 4°C until elemental analysis was completed.
[0066] Inventive Example 9: TF-125 Processing
[0067] SF was first degummed and dissolved as described in Example 6. The TFF system was the same as in Example 6.
[0068] Using a TFF system, the solution was concentrated from 5% (w / v) to 10% (w / v) SF. Continuous diafiltration was performed at 10% (w / v) SF to remove lithium bromide. The silk fibroin was diafiltered for a total of 10 dialysis volumes with DI water replacing the feed. After the fifth dialysis volume, the silk fibroin feed solution was quickly adjusted to pH 4 with hydrochloric acid. The remaining dialysis volume was completed while maintaining a pH of 4. The solution was then concentrated to half of its diafiltration volume and collected. After TFF, the solution was adjusted back to pH 8.5 to 9.0 using sodium hydroxide and filtered through an approximately 1 μm cellulose filter and stored at 4°C until elemental analysis was completed.
[0069] Inventive Example 10: TF-126 Processing
[0070] SF was first degummed and dissolved as described in Example 6. The TFF system was the same as in Example 6.
[0071] Using a TFF system, the solution was concentrated from 5% (w / v) to 10% (w / v) SF. Continuous diafiltration was performed at 10% (w / v) SF to remove lithium bromide. The silk fibroin was first diafiltration filtered for 5 dialysis volumes with DI water as the feed alternative. The silk fibroin was then diafiltration filtered for 5 additional dialysis volumes with 150 mM sodium chloride solution as the feed alternative, for a total of 10 dialysis volumes. The solution was then concentrated to half of its diafiltration volume and collected. After TFF, the solution was filtered through an approximately 1 μm cellulose filter and stored at 4°C until elemental analysis was completed.
[0072] Inventive Example 11: TF-127 Processing
[0073] SF was first degummed and dissolved as described in Example 6. The TFF system was the same as in Example 6.
[0074] The silk fibroin and lithium bromide solution was first adjusted to pH 4 with hydrochloric acid. Using a TFF system, the solution was concentrated from 5% (w / v) to 10% (w / v) SF while maintaining a pH of 4. Continuous diafiltration was performed at 10% (w / v) SF to remove lithium bromide. The silk fibroin was diafiltered for 10 dialysis volumes with DI water replacing the feed. The silk fibroin and lithium bromide solution maintained a pH of 4 in the first five dialysis volumes. After the fifth dialysis volume, the silk fibroin solution was quickly adjusted to a pH of 8.5 to 9.0 using sodium hydroxide. The silk fibroin was then diafiltered for the last five dialysis volumes. The solution was then concentrated to half of its diafiltration volume and collected. After TFF, the solution was filtered through an approximately 1 μm cellulose filter and stored at 4°C until elemental analysis was completed.
[0075] Inventive Example 12: TF-128 Processing
[0076] SF was first degummed and dissolved as described in Example 6. The TFF system was the same as in Example 6.
[0077] Using a TFF system, the solution was concentrated from 5% (w / v) to 10% (w / v) SF. Continuous diafiltration was performed at 10% (w / v) SF to remove lithium bromide. Silk fibroin was first diafiltered for 5 dialysis volumes with an alternative feed of 150 mM sodium chloride aqueous solution. The silk fibroin was then diafiltered for an additional 5 dialysis volumes with an alternative feed of DI water. The solution was then concentrated to half of its diafiltration volume and collected. After TFF, the solution was filtered through an approximately 1 μm cellulose filter and stored at 4°C until elemental analysis was completed.
[0078] Inventive Example 13: TF-129 Processing
[0079] SF was first degummed and dissolved as described in Example 6. The TFF system was the same as in Example 6.
[0080] Using the TFF system, the solution was concentrated from 5% (w / v) to 10% (w / v) SF. Continuous diafiltration was performed at 10% (w / v) SF to remove lithium bromide. The silk fibroin was diafiltered for a total of 10 dialysis volumes with DI water replacing the feed. After the third dialysis volume, the silk fibroin solution was quickly adjusted to a pH of 4 using hydrochloric acid. The silk fibroin was diafiltered for 4 dialysis volumes while maintaining a pH of 4. After the seventh dialysis volume, the silk fibroin solution was quickly adjusted to a pH of 8.5 to 9.0 using sodium hydroxide. The silk fibroin was then diafiltered for the last 3 dialysis volumes. The solution was then concentrated to half of its diafiltration volume and collected. After TFF, the solution was filtered through an approximately 1 μm cellulose filter and stored at 4°C until elemental analysis was completed.
[0081] Results: Elemental analysis of samples prepared in Comparative Examples 1-6 and Inventive Examples 7-13
[0082] The samples were subjected to elemental analysis. The method for determining bromine consisted of weighing an aliquot of 0.10-0.15 grams of the silk fibroin sample in solution into a 40 mL centrifuge tube. 1 mL of tetramethylammonium hydroxide (TMAH) was added, and the sample was heated at 90°C overnight. After the sample cooled to room temperature, 24 mL of DI water was added, the sample was shaken for 1 hour, and then analyzed by inductively coupled plasma mass spectrometry (ICP-MS).
[0083] The method for determining lithium consists of weighing an aliquot of the silk fibroin sample in 1 mL of solution into a polytetrafluoroethylene digestion tube. 2 mL of 2% nitric acid is added and the solution is allowed to react. An additional 2 mL of 0.5% perchloric acid is then added and the tube is heated to 180°C to evaporate the nitric acid and complete the digestion. The solution is then diluted to a final volume of 20 mL by adding DI water. The sample is then diluted 10-fold with DI water and analyzed by ICP-MS. Ion levels are quantified by standard curves for each element.
[0084] The element levels of each batch were then standardized relative to the amount of silk fibroin in each sample solution and reported as lithium or bromine ppm / silk fibroin (or Li or Br mg / kg silk fibroin). The results are shown in the table below. Below is also a detailed description of the flux results of the TFF process performed in Examples 6 and 9-13 and the pH and conductivity values of the silk fibroin and lithium bromide feed solutions.
[0085] Table 1 shows a summary of the elemental analysis data.
[0086] Table 1: Summary of elemental analysis data
[0087]
[0088]
[0089] As shown in Table 1, the different methods used in these TFF experiments result in significant changes in the amount of lithium and bromine in the resulting silk fibroin solution. Comparative Examples 1-5 all use dialysis for desalination. Each of Comparative Examples 1-5 has a lithium concentration of 741-2530ppm (standardized with ppm / kg silk fibroin), and the bromine content is significantly lower. Unexpectedly, not only can dialysis not remove lithium and bromine, but lithium is more easily retained than bromine. Without being bound by theory, it is believed that the charged state of silk fibroin promotes the binding and attraction of lithium ions, making it difficult or impossible to remove by passive or static dialysis, or even in a continuous TFF process. Only by changing the configuration of silk fibroin or promoting another thermodynamic state can lithium be removed and a more complete purity of silk fibroin products be ensured. It is also worth noting that lithium is preferentially retained whether it is degummed in 0.02M sodium carbonate or in 0.5M sodium carbonate.
[0090] Comparative Example 6 is a degumming and desalting method similar to Example 34 of WO 2020 / 247594. Continuous TFF includes pumping silk fibroin and lithium bromide solution to a semipermeable membrane, forcing water, lithium ions, bromide ions, and a very small amount of silk fibroin suitable for passing through the pores out. As the test proceeds, the solution (permeate) lost through the membrane is measured and replaced simultaneously. As described in Example 30 of WO 2020 / 247594, this alternative feed is usually DI water. As shown in Table 1, TFF is performed in water, similar to dialysis, resulting in preferential retention of lithium ions compared to bromine.
[0091] In Examples 7-13, degumming is performed as described in Example 30 of WO 2020 / 247594, but TFF is performed in a salt solution or a low pH solution instead of or in addition to water. Without being bound by theory, the pH reduction method is selected as a method for changing the conformation of silk fibroin by lowering it below its isoelectric point, which is believed to expose some of the bound lithium and bromine in the conformation for replacement. In addition, without being bound by theory, salt substitutes are selected to potentially provide silk fibroin with safer, more chemically attractive binding ions, forcing any residual lithium or bromine bound to the protein to disengage. It is also important to note that degumming according to Comparative Examples 1-4 provides silk fibroin preparations that cannot be processed by TFF at a concentration of 5-10% silk fibroin. Degumming at high sodium carbonate and low temperature allows the TFF process to be performed at high silk fibroin concentrations. Without being bound by theory, it is believed that when the silk fibroin concentration is low, such as 1% w / v, the large volume used to filter the same amount of silk fibroin causes protein instability. Furthermore, the use of 1% w / v silk fibroin resulted in instabilities manifested as irreversible precipitation. Advantageously, performing TFF with 5-10% w / v silk fibroin eliminated many of the problems that arise from using more dilute solutions.
[0092] Comparing the amount of lithium in the samples, as shown in Table 1, the method of the present invention (Examples 7-13) results in a reduction in lithium content compared to the previous TFF method (Comparative Example 6) and Comparative Examples 1-5. Comparative Examples 1 and 2 were selected as examples of the most common silk fibroin solution processing methods in the art. Comparative Examples 3 and 4 were selected as examples of processes that specifically require low levels of inorganic impurities (lithium and bromide) for production. Comparative Example 5 was selected to demonstrate that the desalination process is an important part of the process (rather than the degumming step) regarding elemental impurity levels. All of these processes showed similar levels of lithium and bromide content, standardized relative to the amount of silk fibroin, with a total impurity level range of 813-2554ppm.
[0093] Comparative Example 6 represents a TFF process as described previously. This process exhibited similar elemental impurity levels as Comparative Examples 1-5.
[0094] In Inventive Examples 7, 10 and 12, 150 mM sodium chloride was used in the TFF process. Compared to Example 6 (TFF with water only), Example 7 showed a decrease in lithium, but a sharp increase in bromine. Compared to Example 7, Example 10 showed a more significant decrease in lithium and bromide. This may be due to the addition of an additional 3 dialysis volumes of water / sodium chloride in these batches compared to Example 7. Example 12 represents the opposite of Example 10, where the change occurred in the first 5 dialysis volumes, rather than in the last 5 dialysis volumes. Therefore, the order of the dialysis volumes of the alternative feeds of water or saline solution can affect the final product.
[0095] In Inventive Examples 8, 9, 11 and 13, a reduced pH was used in the TFF process. Compared to Example 6 (TFF with water only), Example 8 showed a reduction in lithium, but a dramatic increase in bromine. The pH change appears to be a more effective way to reduce lithium than adding salt, but the total impurity content in Examples 7 and 8 remains comparable to Example 6. However, the ratio of lithium to bromide has changed dramatically, which has an impact on the safety and elemental binding of silk fibroin.
[0096] Example 9 shows a more significant reduction in lithium compared to Example 8. This may be due to the addition of 3 additional dialysis volumes in these batches compared to Example 8. Changing the pH in the manner of Example 9 results in a more complete reduction of elemental impurities.
[0097] Example 11 represents the opposite of Example 9, where the change occurs in the first 5 dialysis volumes, rather than the last 5 dialysis volumes. Example 11 only shows a reduction in lithium when DI water is used as a feed replacement, so DI water feed replacement can be used to adjust the relative levels of lithium and bromine.
[0098] Example 13 demonstrates the reduction of lithium when a pH change is caused. Example 13 runs 3 dialysis volumes at pH 8-9, then runs 4 dialysis volumes at pH 4, and finally runs 3 dialysis volumes again at pH 8-9. For comparison, Example 11 runs 5 dialysis volumes at pH 4, then runs 5 dialysis volumes at pH 8-9. As described in Example 13, when the process includes first dialyzing at pH 8-9, the lithium content is more effectively reduced. The bromine level between the two remains unchanged, although the ratio of the two changes significantly. Therefore, in the optimized process, multiple dialysis volumes at unregulated pH are followed by multiple dialysis volumes at low pH, all of which have an alternative feed of water. The alternative feed of sodium chloride solution shows some reduction in lithium and some increase in bromine, indicating that it is useful when the pH value cannot be changed or if different combinations of ion species are attempted to be attached to silk fibroin. The ability to vary the ratio of lithium to bromine suggests that the process can be adapted to a variety of desired ratios, and that other elements can be incorporated into the silk fibroin as the ionic species pass through the TFF process.
[0099] Table 2 shows the pH values of silk fibroin and lithium bromide solutions during TFF.
[0100] Table 2: pH values of silk fibroin and lithium bromide solutions during TFF
[0101] Example 6 Example 9 Example 10 Embodiment 11 Example 12 Embodiment 13 pH at DV3 8.6 8.6 8.6 4.1 8.5 8.7 pH at DV4 8.7 8.7 8.7 4 8.6 4 pH at DV5 8.7 8.7 8.7 4.1 8.6 4 pH at DV6 8.7 4 8.6 8.7 8.7 4 pH at DV7 8.7 4 8.6 8.6 8.7 4 pH at DV8 8.6 4 8.6 8.5 8.7 8.7 pH at DV9 8.6 4.1 8.6 8.5 8.7 8.7 pH at DV10 8.5 4 8.6 8.4 8.6 8.6 Final pH 8.6 8.8 8.5 8.4 8.6 8.6
[0102] Table 3 shows the conductivity values (ppm) of silk fibroin and lithium bromide solutions during TFF:
[0103] Table 3: Conductivity values of silk fibroin and lithium bromide solutions during TFF (ppm)
[0104] Example 6 Example 9 Example 10 Embodiment 11 Example 12 Embodiment 13 Conductivity at DV3 Overrun Overrun Overrun Overrun Overrun Overrun Conductivity at DV4 2020 1670 1900 2290 Overrun 2460 Conductivity at DV5 830 730 760 950 Overrun 1050 Conductivity at DV6 420 720 Overrun 740 Overrun 460 Conductivity at DV7 410 280 Overrun 460 1440 230 Conductivity at DV8 400 130 Overrun 430 700 540 Conductivity at DV9 380 60 Overrun 430 500 480 Conductivity at DV10 380 40 Overrun 410 470 490 Final conductivity 560 810 Overrun 630 690 710
[0105] Table 4 shows the permeate flux values (LMH) during the TFF process:
[0106] Table 4: Permeate flux values (LMH) during TFF process
[0107] Example 6 Example 9 Example 10 Embodiment 11 Example 12 Embodiment 13 Flux at DV1 14.13 14.68 14.96 14.96 14.68 14.40 Flux at DV2 15.90 14.96 14.68 15.57 15.90 14.13 Flux at DV3 16.24 15.57 15.57 16.24 15.90 16.24 Flux at DV4 16.24 16.24 15.90 16.75 16.59 17.34 Flux at DV5 16.59 15.57 14.40 15.57 16.24 17.34 Flux at DV6 14.96 16.24 16.24 15.90 16.24 16.96 Flux at DV7 14.13 15.57 16.96 14.40 16.96 16.59 Flux at DV8 12.72 16.59 16.59 13.16 16.59 14.96 Flux at DV9 13.16 16.24 17.34 13.16 14.96 13.63 Flux at DV10 13.63 16.59 16.96 13.39 13.63 13.16
[0108] Table 5 shows the permeate flux data from Table 4, expressed as the change relative to the control batch of Example 6 at each dialysis volume:
[0109] Table 5: Permeate flux data from Table 4, expressed as change per dialysis volume relative to the control batch of Example 6
[0110] Example 6 Example 9 Example 10 Embodiment 11 Example 12 Embodiment 13 Flux at DV1 - 3.89% 5.87% 5.87% 3.89% 1.91% Flux at DV2 - -5.91% -7.67% -2.08% 0.00% -11.13% Flux at DV3 - -4.13% -4.13% 0.00% -2.09% 0.00% Flux at DV4 - 0.00% -2.09% 3.14% 2.16% 6.77% Flux at DV5 - -6.15% -13.20% -6.15% -2.11% 4.52% Flux at DV6 - 8.56% 8.56% 6.28% 8.56% 13.37% Flux at DV7 - 10.19% 20.03% 1.91% 20.03% 17.41% Flux at DV8 - 30.42% 30.42% 3.46% 30.42% 17.61% Flux at DV9 - 23.40% 31.76% 0.00% 13.68% 3.57% Flux at DV10 - 21.72% 24.43% -1.76% 0.00% -3.45%
[0111] Tables 4 and 5 quote the flux (in liters / m 2 The flux is expressed in units of membrane surface area / hour or LMH), the flux being measured during half of the dialysis volume until the time at which the desired mass is reached. Table 5 shows the percentage increase or decrease compared to the control experiment (Example 6). Directly related to the new method, or discovered in hindsight, Examples 9, 10, 12 and 13 all show an increase of 10% or more for various dialysis volumes. Under standard conditions (a process of 10 dialysis volumes of DI water), the flux steadily decreases after DV5 until the end of the experiment. After starting the process in the same way, this decrease in flux can be avoided if the pH is lowered or sodium chloride is introduced. This is a secondary benefit of these methods, in addition to the improvement in reducing elemental impurities.
[0112] When pH reduction method and sodium chloride alternative method are used at the end or in the middle of the test, the improvement of flux is similar. However, Example 11 and Example 12 show the variability of these results. Example 11 shows that flux does not improve in the test process, which may be because the material is adjusted to pH 4 before the initial concentration step. Example 12 shows that the increase of flux is during dialysis volume 6, 7, 8 and 9, but returns to a lower value when dialysis volume 10. In this test, sodium chloride is used as a substitute for the first five dialysis volumes, and then DI water is used. When sodium chloride is used, the flux of the dialysis volume does not increase. This shows that when most of lithium and bromine are removed, the flux is the highest, but the test solution still contains at least some sodium and chlorine. When sodium and chlorine are removed, the solution returns to the aqueous solution with only silk fibroin, and the flux is reduced to the value in the control test again.
[0113] Another phenomenon observed during the TFF process at pH 4 further confirms the novelty and unexpected nature of these results. After the pH of the silk fibroin solution was adjusted to 4, the solution immediately became turbid. This turbidity began to appear at a pH of about 5-6 and persisted when the pH was maintained at 4. Without being bound by theory, it is believed that this turbidity represents that the silk fibroin molecules become insoluble and are produced from the solution. In Example 7, from DV5 to DV10, the turbidity becomes more obvious. Importantly, this insolubility is reversible. After the pH is adjusted back to 7-9, the particles will all return to the solution. This can be observed in Table 3 of Example 7. The conductivity decreases continuously from DV5 to DV10, while the pH is maintained at 4, and the solution is turbid. This is because the elemental impurities are filtered out, the silk fibroin is precipitated, and no longer appears to be soluble. When the pH of the solution is adjusted back to above 8.5, the conductivity increases toward the conductivity of other batches, indicating that the silk fibroin has been completely returned to the solution. This effect can also be seen in the transition between DV7 and DV8 in Example 13, where conductivity increases after pH adjustment (which is a combination of the introduction of sodium hydroxide and the dissolution of silk fibroin). Counterintuitively, this turbidity results in more efficient lithium reduction and increased flux.
[0114] Without being bound by theory, it is believed that this reversible insolubility is important for reducing the amount of bromine in solution. This is evident in the fact that the sodium chloride method does not result in this turbidity, and also results in a slight increase in bromine. The standard method of replacing with water at high pH is relatively effective in removing bromine, but improves in experiments with lower pH. It is also shown in Table 1 that when these new methods are used throughout the experiment (7 dialysis volumes), bromine levels increase by 19.0 times (sodium chloride replacement) or 20.2 times (pH is 4) compared to the control batch. They are also accompanied by a 5.3-fold (sodium chloride replacement) or 18.4-fold (pH is 4) reduction in lithium.
[0115] This reversible precipitation by pH change or the method for preferential element exchange using sodium chloride solution or equivalent is also feasible for other chaotropic agents that can dissolve solid silk fibroin.These chaotropic agents can include but are not limited to lithium bromide, lithium chloride, calcium chloride, ethanol, guanidine chloride or urea.If these compounds help to dissolve silk fibroin after degumming, it is possible that the method described herein can affect the element impurity content of final silk solution in a similar manner.The flux increase caused by the method described herein can also be reproduced, because this seems to be the most common at the end of the test (most of the chaotropic agents will be removed in any case).Therefore, even using different solubilizing agents, the flux increased by pH value change or adding sodium chloride solution may also be repeatable.
[0116] In addition, due to the reduction of calcium impurities in the silk solution after dissolution with a mixture of calcium chloride and ethanol, the formulation of phosphate-containing buffers and solutions is now possible. Previously, after the standard dialysis step, too much calcium remained and the calcium phosphate would precipitate after formulation, making the stability and regulation of the material impossible. However, after these improved processes, the calcium is reduced to a level that formulations with no significant precipitation in phosphate-buffered saline solutions are possible. This will greatly increase the usefulness and applicability of silk materials in biomedical applications.
[0117] Therefore, it was shown that the efficiency of TFF purification of silk fibroin solution was improved by introducing salt solution into the alternative feed during the TFF process.
[0118] It was also shown that changing the pH of the retentate silk fibroin solution in a very specific and unexpected way would also improve the efficiency of the TFF filtration process.
[0119] The introduction of salt solutions and changes in pH can also be combined to improve the efficiency of the TFF process.
[0120] The new TFF process described herein also allows reversible precipitation of silk fibroin solutions, which allows for increased elemental exchange and improved TFF permeate flux. Using the new process, TFF flux can be increased by 5% or more in one or more dialysis volumes.
[0121] The new TFF process also allows for a significant reduction in the final elemental content of one or more lytic or chaotropic agents by a factor of 5 or more compared to conventional methods.
[0122] Inventive Example 14: TF-137 Processing
[0123] SF was first degummed, dissolved, diluted and filtered as described in Example 6. Single 0.11 m of 5 kDa membrane 2 LiBr was removed using a 3-pack tangential flow filtration (TFF) system. Before introducing SF into the system, the system was washed with DI water and sterilized with 0.1N sodium hydroxide. The system was then flushed with water to remove the sodium hydroxide. A 0.11 m 2 All TFF of the membrane is 4LMM (liter / m 2 The membrane was run at a flow rate of (membrane area / min).
[0124] Using a TFF system, the solution was concentrated from 5% (w / v) to 10% (w / v) SF. Continuous diafiltration was performed at 10% (w / v) SF to remove lithium bromide. The silk fibroin was diafiltered for 10 dialysis volumes with an alternative feed of DI water. The solution was then concentrated to half of its diafiltration volume and collected. After TFF, the solution was stored at 4°C until elemental analysis was completed.
[0125] Inventive Example 15: TF-140 Processing
[0126] SF was first degummed, dissolved, diluted and filtered as described in Example 6. The TFF system was the same as in Example 14.
[0127] Using a TFF system, the solution was concentrated from 5% (w / v) to 10% (w / v) SF. Continuous diafiltration was performed at 10% (w / v) SF to remove lithium bromide. The silk fibroin was diafiltered for 10 dialysis volumes with DI water replacing the feed. After the fifth dialysis volume, the silk fibroin solution was quickly adjusted to pH 2 using hydrochloric acid. The silk fibroin was then diafiltered for the final 5 dialysis volumes while maintaining a pH of 2. The solution was then concentrated to half of its diafiltration volume and collected. After TFF, the pH of the solution was adjusted back to 8.5 to 9.0 using sodium hydroxide and stored at 4°C until elemental analysis was completed.
[0128] Inventive Example 16: TF-139 Processing
[0129] SF was first degummed, dissolved, diluted and filtered as described in Example 6. The TFF system was the same as in Example 14.
[0130] Using a TFF system, the solution was concentrated from 5% (w / v) to 10% (w / v) SF. Continuous diafiltration was performed at 10% (w / v) SF to remove lithium bromide. The silk fibroin was diafiltered for 10 dialysis volumes with DI water replacing the feed. After the fifth dialysis volume, the silk fibroin solution was quickly adjusted to pH 3 using hydrochloric acid. The silk fibroin was then diafiltered for the last 5 dialysis volumes while maintaining a pH of 3. The solution was then concentrated to half of its diafiltration volume and collected. After TFF, the pH of the solution was adjusted back to 8.5 to 9.0 using sodium hydroxide and stored at 4°C until elemental analysis was completed.
[0131] Inventive Example 17: TF-138 Processing
[0132] SF was first degummed, dissolved, diluted and filtered as described in Example 6. The TFF system was the same as in Example 14.
[0133] Using a TFF system, the solution was concentrated from 5% (w / v) to 10% (w / v) SF. Continuous diafiltration was performed at 10% (w / v) SF to remove lithium bromide. The silk fibroin was diafiltered for 10 dialysis volumes with DI water replacing the feed. After the fifth dialysis volume, the silk fibroin solution was quickly adjusted to pH 4 using hydrochloric acid. The silk fibroin was then diafiltered for the last 5 dialysis volumes while maintaining a pH of 4. The solution was then concentrated to half of its diafiltration volume and collected. After TFF, the pH of the solution was adjusted back to 8.5 to 9.0 using sodium hydroxide and stored at 4°C until elemental analysis was completed.
[0134] Inventive Example 18: TF-141 Processing
[0135] SF was first degummed, dissolved, diluted and filtered as described in Example 6. The TFF system was the same as in Example 14.
[0136] Using a TFF system, the solution was concentrated from 5% (w / v) to 10% (w / v) SF. Continuous diafiltration was performed at 10% (w / v) SF to remove lithium bromide. The silk fibroin was diafiltered for 10 dialysis volumes with DI water replacing the feed. After the fifth dialysis volume, the silk fibroin solution was quickly adjusted to pH 5 using hydrochloric acid. The silk fibroin was then diafiltered for the last 5 dialysis volumes while maintaining a pH of 5. The solution was then concentrated to half of its diafiltration volume and collected. After TFF, the pH of the solution was adjusted back to 8.5 to 9.0 using sodium hydroxide and stored at 4°C until elemental analysis was completed.
[0137] Inventive Example 19: TF-142 Processing
[0138] SF was first degummed, dissolved, diluted and filtered as described in Example 6. The TFF system was the same as in Example 14.
[0139] Using a TFF system, the solution was concentrated from 5% (w / v) to 10% (w / v) SF. Continuous diafiltration was performed at 10% (w / v) SF to remove lithium bromide. The silk fibroin was diafiltered for 10 dialysis volumes with DI water replacing the feed. After the fifth dialysis volume, the silk fibroin solution was quickly adjusted to pH 6 using hydrochloric acid. The silk fibroin was then diafiltered for the final 5 dialysis volumes while maintaining a pH of 6. The solution was then concentrated to half of its diafiltration volume and collected. After TFF, the pH of the solution was adjusted back to 8.5 to 9.0 using sodium hydroxide and stored at 4°C until elemental analysis was completed.
[0140] Inventive Example 20: TF-143 Processing
[0141] SF was first degummed, dissolved, diluted and filtered as described in Example 6. The TFF system was the same as in Example 14.
[0142] Using a TFF system, the solution was concentrated from 5% (w / v) to 10% (w / v) SF. Continuous diafiltration was performed at 10% (w / v) SF to remove lithium bromide. The silk fibroin was diafiltered for 10 dialysis volumes with DI water replacing the feed. After the fifth dialysis volume, the silk fibroin solution was quickly adjusted to pH 7 using hydrochloric acid. The silk fibroin was then diafiltered for the final 5 dialysis volumes while maintaining a pH of 7. The solution was then concentrated to half of its diafiltration volume and collected. After TFF, the pH of the solution was adjusted back to 8.5 to 9.0 using sodium hydroxide and stored at 4°C until elemental analysis was completed.
[0143] Inventive Example 21: TF-145 Processing
[0144] SF was first degummed, dissolved, diluted and filtered as described in Example 6. The TFF system was the same as in Example 14.
[0145] Using a TFF system, the solution was concentrated from 5% (w / v) to 10% (w / v) SF. Continuous diafiltration was performed at 10% (w / v) SF to remove lithium bromide. The silk fibroin was diafiltered for 10 dialysis volumes with DI water replacing the feed. After the third dialysis volume, the silk fibroin solution was quickly adjusted to pH 4 using hydrochloric acid. The silk fibroin was then diafiltered for the final 7 dialysis volumes while maintaining a pH of 4. The solution was then concentrated to half of its diafiltration volume and collected. After TFF, the pH of the solution was adjusted back to between 8.5 and 9.0 using sodium hydroxide and stored at 4°C until elemental analysis was completed.
[0146] Inventive Example 22: TF-144 Processing
[0147] SF was first degummed, dissolved, diluted and filtered as described in Example 6. The TFF system was the same as in Example 14.
[0148] Using a TFF system, the solution was concentrated from 5% (w / v) to 10% (w / v) SF. Continuous diafiltration was performed at 10% (w / v) SF to remove lithium bromide. The silk fibroin was diafiltered for 10 dialysis volumes with DI water replacing the feed. After the fourth dialysis volume, the silk fibroin solution was quickly adjusted to pH 4 using hydrochloric acid. The silk fibroin was then diafiltered for the final 6 dialysis volumes while maintaining a pH of 4. The solution was then concentrated to half of its diafiltration volume and collected. After TFF, the pH of the solution was adjusted back to 8.5 to 9.0 using sodium hydroxide and stored at 4°C until elemental analysis was completed.
[0149] Inventive Example 23: TF-146 Processing
[0150] SF was first degummed, dissolved, diluted and filtered as described in Example 6. The TFF system was the same as in Example 14.
[0151] Using a TFF system, the solution was concentrated from 5% (w / v) to 10% (w / v) SF. Continuous diafiltration was performed at 10% (w / v) SF to remove lithium bromide. The silk fibroin was diafiltered for 10 dialysis volumes with DI water replacing the feed. After the sixth dialysis volume, the silk fibroin solution was quickly adjusted to pH 4 using hydrochloric acid. The silk fibroin was then diafiltered for the last 4 dialysis volumes while maintaining a pH of 4. The solution was then concentrated to half of its diafiltration volume and collected. After TFF, the pH of the solution was adjusted back to 8.5 to 9.0 using sodium hydroxide and stored at 4°C until elemental analysis was completed.
[0152] Inventive Example 24: TF-147 Processing
[0153] SF was first degummed, dissolved, diluted and filtered as described in Example 6. The TFF system was the same as in Example 14.
[0154] Using a TFF system, the solution was concentrated from 5% (w / v) to 10% (w / v) SF. Continuous diafiltration was performed at 10% (w / v) SF to remove lithium bromide. The silk fibroin was diafiltered for 10 dialysis volumes with DI water replacing the feed. After the seventh dialysis volume, the silk fibroin solution was quickly adjusted to pH 4 using hydrochloric acid. The silk fibroin was then diafiltered for the last 3 dialysis volumes while maintaining a pH of 4. The solution was then concentrated to half of its diafiltration volume and collected. After TFF, the pH of the solution was adjusted back to 8.5 to 9.0 using sodium hydroxide and stored at 4°C until elemental analysis was completed.
[0155] Inventive Example 25: TF-148 Processing
[0156] SF was first degummed, dissolved, diluted and filtered as described in Example 6. The TFF system was the same as in Example 14.
[0157] Using a TFF system, the solution was concentrated from 5% (w / v) to 10% (w / v) SF. Continuous diafiltration was performed at 10% (w / v) SF to remove lithium bromide. Silk fibroin was first diafiltered for 5 dialysis volumes using DI water as an alternative feed. Silk fibroin was then diafiltered for 5 additional volumes using 150 mM sodium chloride solution as an alternative feed, for a total of 10 dialysis volumes. The solution was then concentrated to half of its diafiltration volume and collected. After TFF, the solution was stored at 4°C until elemental analysis was completed.
[0158] Inventive Example 26: TF-149 Processing
[0159] SF was first degummed, dissolved, diluted and filtered as described in Example 6. The TFF system was the same as in Example 14.
[0160] Using a TFF system, the solution was concentrated from 5% (w / v) to 10% (w / v) SF. Continuous diafiltration was performed at 10% (w / v) SF to remove lithium bromide. Silk fibroin was first diafiltered for 5 dialysis volumes using DI water as an alternative feed. Silk fibroin was then diafiltered for 5 additional volumes using 150 mM calcium chloride solution as an alternative feed, for a total of 10 dialysis volumes. The solution was then concentrated to half of its diafiltration volume and collected. After TFF, the solution was stored at 4°C until elemental analysis was completed.
[0161] Inventive Example 27: TF-150 Processing
[0162] SF was first degummed, dissolved, diluted and filtered as described in Example 6. The TFF system was the same as in Example 14.
[0163] Using a TFF system, the solution was concentrated from 5% (w / v) to 10% (w / v) SF. Continuous diafiltration was performed at 10% (w / v) SF to remove lithium bromide. The silk fibroin was first diafiltration filtered for 5 dialysis volumes with DI water as the feed substitute. The silk fibroin was then diafiltration filtered for 5 additional volumes with 150 mM calcium chloride solution as the feed substitute, for a total of 10 dialysis volumes. After the fifth dialysis volume, the silk fibroin solution was adjusted to a pH of 4 using hydrochloric acid. The pH was maintained at 4 during the last five dialysis volumes with calcium chloride. The solution was then concentrated to half of its diafiltration volume and collected. After TFF, the pH of the solution was adjusted back to 8.5 to 9.0 using sodium hydroxide and stored at 4°C until elemental analysis was completed.
[0164] Inventive Example 28: TF-151 Processing
[0165] SF was first degummed, dissolved, diluted and filtered as described in Example 6. The TFF system was the same as in Example 14.
[0166] Using a TFF system, the solution was concentrated from 5% (w / v) to 10% (w / v) SF. Continuous diafiltration was performed at 10% (w / v) SF to remove lithium bromide. Silk fibroin was first diafiltered for 5 dialysis volumes with DI water as the feed replacement. Silk fibroin was then diafiltered for 5 additional volumes with 150 mM magnesium chloride solution as the feed replacement, for a total of 10 dialysis volumes. The solution was then concentrated to half of its diafiltration volume and collected. After TFF, the solution was stored at 4°C until elemental analysis was completed.
[0167] Table 6: Results of Examples 14-28
[0168]
[0169]
[0170] Inventive Examples 14-28 elaborate on the parameters of the methods described in Examples 1-13. For Examples 14-37, lithium was determined according to US EPA Method 200.7, Version 4.4, "Determination of Metals and Trace Elements in Water and Wastes by Inductively Coupled Plasma-Atomic Emission Spectrometry", and bromide was determined according to US EPA Method 300.0, Version 2.1, "Determination of Inorganic Anions by Ion Chromatography". Calcium was determined for Examples 29-31 in a manner similar to lithium in Examples 1-13.
[0171] Embodiment 14-28 only focuses on lithium, because lithium is the more relevant impurity that proves the safety of silk fibroin component. Embodiment 14 provides the control group of diafiltration silk fibroin solution, and it has the alternative feed of water, and does not change the retentate. Embodiment 15-20 shows the pH value range of retentate. In each case, the solution is diafiltration 5 dialysis volumes, pH is unchanged, and then the pH when the remaining 5 dialysis volumes is reduced. pH value includes 2,3,4,5,6 and 7. For each pH value, lithium reduction multiple is 67 times, 77 times, 37 times, 3.2 times, 1.8 times and 1.4 times respectively. When pH value is 4 to 5, the efficiency of this method has great variation. This corresponds to the isoelectric point of reported silk fibroin (usually listed as 4.0-4.5). Not bound by theory, when the silk fibroin retentate solution is lower than its isoelectric point, it seems to preferentially release cationic lithium, but when it is higher than its isoelectric point, it seems to preferentially release anionic bromine. This would potentially explain why standard dialysis methods have much more lithium than bromine, as silk fibroin is generally slightly alkaline in solution. Therefore, the most ideal processing method to reduce elemental impurities would need to include diafiltration or dialysis time on both sides of the silk fibroin isoelectric point.
[0172] Examples 21-24 elaborate on the introduction of pH changes during the diafiltration process. A pH of 4 was selected as the ideal pH. At an unchanged higher pH of 8.5-9.0, pH changes were introduced after 3, 4, 5 (Example 17), 6, and 7 dialysis volumes. Each trial showed similar reduced lithium content compared to the control group. These are all viable options for improving the TFF process in terms of lithium reduction. The timing of the pH change may affect the bromine level.
[0173] Examples 25-28 tested different alternative feeds. These alternative feeds included 150 mM sodium chloride solution, 150 mM calcium chloride solution, and 150 mM magnesium chloride solution. All of these solutions were introduced midway through the diafiltration after 5 dialysis volumes were performed with pure water as the alternative feed. In addition, as shown in Example 27, the calcium chloride alternative feed was combined with a change in the retentate pH to 4 to determine if there was any synergistic effect. There did not appear to be any significant differences in the reduction of lithium in these groups. All of these showed similar or greater reductions than those shown by the pH change method. All of these salts are viable options for improving the TFF process, and it is reasonable to assume that other similar salts can be used just as effectively.
[0174] Inventive Example 29: TF-132 Processing
[0175] SF was first degummed as described in Example 6. To dissolve the degummed SF fibers, 500 g of degummed SF was placed in a 1-gallon glass jar along with 2 L of Ajisawa reagent. Ajisawa reagent is a solution consisting of calcium chloride, ethanol, and water in a molar ratio of 1:2:8, respectively. The jar was incubated at 80°C overnight to dissolve the SF fibers. Prior to tangential flow filtration, the silk fibroin solution was diluted from 20% (w / v) SF to 5% (w / v) SF with DI water. The diluted solution was then filtered through a cellulose membrane of approximately 5 μm to remove any residual particles. The TFF system was the same as in Example 6.
[0176] Using a TFF system, the solution was concentrated from 5% (w / v) to 10% (w / v) SF. Continuous diafiltration was performed at 10% (w / v) SF to remove lithium bromide. The silk fibroin was diafiltered for a total of 10 dialysis volumes with DI water replacing the feed. The solution was then concentrated to half of its diafiltration volume and collected. After TFF, the solution was filtered through an approximately 1 μm cellulose filter and stored at 4°C until elemental analysis was completed.
[0177] Inventive Example 30: TF-134 Processing
[0178] SF was first degummed as described in Example 6. To dissolve the degummed SF fibers, 350 g of degummed SF was placed in a 1-gallon glass jar along with 3.15 L of Ajisawa reagent. Ajisawa reagent is a solution consisting of calcium chloride to ethanol to water in a molar ratio of 1:2:8, respectively. The jar was incubated at 80°C for 2 hours to dissolve the SF fibers. Prior to tangential flow filtration, the silk fibroin solution was diluted from 10% (w / v) SF to 5% (w / v) SF with DI water. The diluted solution was then filtered through a cellulose membrane of approximately 5 μm to remove any residual particles. The TFF system was the same as in Example 6.
[0179] Using a TFF system, the solution was concentrated from 5% (w / v) to 10% (w / v) SF. Continuous diafiltration was performed at 10% (w / v) SF to remove lithium bromide. The silk fibroin was diafiltered for a total of 10 dialysis volumes using DI water instead of feed. After the silk fibroin was diafiltered for a total of 10 dialysis volumes using DI water instead of feed. After the fifth dialysis volume, the silk fibroin feed solution was quickly adjusted to pH 4 using hydrochloric acid. The remaining dialysis volume was completed while maintaining a pH of 4. The solution was then concentrated to half of its diafiltration volume and collected. After TFF, the pH of the solution was adjusted back to 8.5 to 9.0 using sodium hydroxide and filtered through approximately a 1 μm cellulose filter and stored at 4°C until elemental analysis was completed.
[0180] Inventive Example 31: TF-135 Processing
[0181] SF was first degummed as described in Example 6. SF was dissolved and filtered as described in Example 15. The TFF system was the same as in Example 6.
[0182] Using a TFF system, the solution was concentrated from 5% (w / v) to 10% (w / v) SF. Continuous diafiltration was performed at 10% (w / v) SF to remove lithium bromide. Silk fibroin was first diafiltered with DI water as a substitute feed for a total of 5 diafiltration volumes, and then an additional 5 diafiltration volumes (a total of 10) were diafiltered with a 150 mM aqueous sodium chloride substitute feed. The solution was then concentrated to half of its diafiltration volume and collected. After TFF, the solution was filtered through an approximately 1 μm cellulose filter and stored at 4°C until elemental analysis was completed.
[0183] Table 7: Results of Examples 29-31
[0184]
[0185] Embodiment 29-31 proves the applicability of chaotropic agent other than lithium bromide to these processes.In this case, the mixture of calcium chloride, ethanol and water is used.Example 29 is a standard TFF method, which does not change the retentate and pure water substitutes the feed.Example 30 includes reducing the pH of the retentate to 4 midway in the diafiltration, and embodiment 31 includes switching to sodium chloride substitutes the feed midway in the diafiltration.Example 30 causes calcium to reduce 60 times, and embodiment 31 causes calcium to reduce 12 times.The pH method seems to be equally helpful to reduce the cation content with this dissolving agent, and the salt solution substitutes the feed less significantly, but is still enough to achieve the benefits mentioned above.
[0186] Comparative Example 32: DSC-SC-20 processing (degumming similar to WO 2020 / 247594, Example 34; desalting as described in Rockwood et al.)
[0187] Silk fibroin is prepared by degumming silk thread in sodium carbonate solution, dissolving in lithium bromide, and purifying by dialysis. 31.3L water and 1.66kg sodium carbonate (0.5M sodium carbonate) are added to a container and heated to 85°C. 2.5kg silk thread is added to the solution. The silk thread is degummed at 85°C for 4 hours. After 4 hours, the silk thread is taken out and rinsed in DI water to remove excess carbonate solution. The silk fibroin fiber is then squeezed to remove water and placed in an oven at 60°C to dry for two days.
[0188] After drying, 30g of silk fibroin was loaded into a 250mL bottle and 120mL of 9.3M lithium bromide was added. The bottle was capped and heated at 60°C overnight (about 20 hours). The resulting 20% (w / v) silk fibroin lithium bromide solution was then poured into a 3.5kDa dialysis cassette and placed in 5L DI water under stirring for dialysis. In the next 48 hours, water was completely exchanged 6 times. After dialysis, the combined solutions were centrifuged at 10000xg for 20 minutes to remove any insoluble particles and stored at 4°C before analysis.
[0189] Inventive Example 33: DSC-SC-21 Processing
[0190] Silk fibroin was degummed and dried as described in Example 32.
[0191] After drying, 30g silk fibroin is loaded into 250mL bottle, and 120mL 9.3M lithium bromide is added. The bottle is covered with a lid, and heated at 60 ℃ overnight (about 20 hours). First, a part is diluted with DI water at 1:1, and then the resulting 10% (w / v) silk fibroin solution is poured into 3.5kDa dialysis cassettes, and placed in 5L DI water under stirring for dialysis. First, a part is diluted with DI water at 1:3, and then the resulting 5% (w / v) silk fibroin solution is poured into 3.5kDa dialysis cassettes, and placed in 5L DI water under stirring for dialysis. First, a part is diluted with DI water at 1:19, and then the resulting 1% (w / v) silk fibroin solution is poured into 3.5kDa dialysis cassettes, and placed in 5L DI water under stirring for dialysis. In the following 48 hours, water was completely exchanged 6 times. After dialysis, the individual solutions were combined, centrifuged at 10,000 xg for 20 minutes to remove any insoluble particles, and stored at 4°C prior to analysis.
[0192] Inventive Example 34: DSC-SC-22 Processing
[0193] Silk fibroin was degummed and dried as described in Example 32.
[0194] After drying, 30g of silk fibroin was loaded into a 250mL bottle and 120mL of 9.3M lithium bromide was added. The bottle was capped and heated at 60°C overnight (about 20 hours). The resulting 20% (w / v) lithium bromide solution of silk fibroin was then poured into a 3.5kDa dialysis box and placed in 5L DI water under stirring for dialysis. In the following 48 hours, water was completely exchanged 6 times. After the third exchange (about 24 hours after the start of dialysis), the silk fibroin solution was taken out of the box, combined, adjusted to pH 4 using hydrochloric acid, and then put back into the box for dialysis. At the subsequent sixth water change, the solution was taken out and the pH value was adjusted to 4 if necessary. After dialysis, the solution was combined, the pH was adjusted back to 8.5 to 9.0 using sodium hydroxide, centrifuged at 10000x g for 20 minutes to remove any insoluble particles, and stored at 4°C before analysis.
[0195] Inventive Example 35: DSC-SC-23 Processing
[0196] Silk fibroin was degummed and dried as described in Example 32.
[0197] After drying, 30g of silk fibroin was loaded into a 250mL bottle and 120mL of 9.3M lithium bromide was added. The bottle was capped and heated at 60°C overnight (about 20 hours). The pH of the solution of 20% (w / v) of silk fibroin in lithium bromide was then adjusted to 4 using hydrochloric acid, poured into a 3.5kDa dialysis cassette, and placed in 5L DI water under stirring for dialysis. In the following 48 hours, water was completely exchanged 6 times. Each time the water was changed, the silk fibroin solution was taken out and, if necessary, the pH was adjusted to 4 before it was put back into the cassette. After dialysis, the solution was combined, the pH was adjusted back to 8.5 to 9.0 using sodium hydroxide, and any insoluble particles were removed by centrifugation at 10000x g for 20 minutes, and stored at 4°C before analysis.
[0198] Inventive Example 36: DSC-SC-24 Processing
[0199] Silk fibroin was degummed and dried as described in Example 32.
[0200] After drying, 30g of silk fibroin was loaded into a 250mL bottle and 120mL of 9.3M lithium bromide was added. The bottle was capped and heated at 60°C overnight (about 20 hours). The resulting 20% (w / v) lithium bromide solution of silk fibroin was then poured into a 3.5kDa dialysis cassette and placed in 5L DI water under stirring for dialysis. In the following 48 hours, water was completely exchanged 6 times. After the third exchange, the dialysis buffer was changed from DI water to 150mM sodium chloride aqueous solution. This was still the dialysis buffer in the final exchange. After dialysis, the combined solution was centrifuged at 10000x g for 20 minutes to remove any insoluble particles and stored at 4°C before analysis.
[0201] Inventive Example 37: DSC-SC-25 Processing
[0202] Silk fibroin was degummed and dried as described in Example 32.
[0203] After drying, 30g of silk fibroin was loaded into a 250mL bottle and 120mL of 9.3M lithium bromide was added. The bottle was capped and heated at 60°C overnight (approximately 20 hours). The resulting 20% (w / v) lithium bromide solution of silk fibroin was then poured into a 3.5kDa dialysis cassette and placed in a 5L 150mM sodium chloride solution under stirring for dialysis. In the following 48 hours, the same salt solution was completely exchanged 6 times. After dialysis, the combined solution was centrifuged at 10000x g for 20 minutes to remove any insoluble particles and stored at 4°C before analysis.
[0204] Table 8: Results of Examples 32-37
[0205]
[0206] * = Not normalized to silk fibroin concentration as the concentration could not be accurately determined. The results listed are the concentrations in the silk solution. However, these results are consistent with Examples 34, 36 and 37 and it is reasonable to assume that the concentrations of silk fibroin were similar to those groups.
[0207] Embodiment 32-37 proves the applicability of these methods of using dialysis to exchange chaotropic salt. Embodiment 32 is the standard method described in the art, wherein the silk fibroin solution in lithium bromide is placed in a dialysis box with a 3.5kDa membrane, and dialyzed with pure water for 48 hours, and 6 complete water exchanges are performed. Embodiment 33 determines that the initial concentration of silk fibroin in lithium bromide has no effect on the element impurity content after dialysis. Embodiment 34 repeats the above-mentioned TFF method, and the pH of the silk fibroin solution is changed to 4 after 3 exchanges and 24 hours, and then the pH value is maintained until the dialysis is completed. This results in a 14-fold reduction in lithium, which is not as significant as the TFF method, but it does prove that the impact will be brought into this salt exchange method. Embodiment 35 is tested for a whole 48 hours with a silk fibroin solution with a pH of 4. This material shows similar element impurity results, but due to gelation, the accurate silk fibroin concentration for standardization cannot be determined.
[0208] Example 36 and Example 37 simulated the salt replacement method by placing the dialysis box in an excess of 150mM sodium chloride solution instead of water for the second half of the dialysis or performing the entire dialysis. Both showed similar 18-fold and 17-fold lithium reduction levels, respectively, while maintaining low bromine. This is an important difference from the TFF method. If the salt replacement feed is maintained throughout the experiment, the bromine level will increase (see Example 7). Without being bound by theory, this difference may be related to the mechanical equipment required for TFF, the different chemical environment of pressurized TFF (rather than static dialysis), or because of the time difference between a few hours of TFF and two days of dialysis.
[0209] The use of the terms "one", "an" and "the" and similar indicators (especially in the context of the following claims) should be interpreted as covering the singular and the plural, unless otherwise specified herein or the context is clearly contradictory. The terms first, second, etc. used herein are not meant to indicate any particular order, but are merely for convenience to indicate multiple, for example, multiple layers. The terms "comprising", "having", "including" and "containing" should be interpreted as open terms (i.e., meaning "including, but not limited to"), unless otherwise specified. The description of the numerical range is intended only to be used as a shorthand method for individually referring to each individual numerical value falling within the range, unless otherwise specified herein, and each individual numerical value is incorporated into this specification as if it is individually described herein. The endpoints of all ranges are included in the range and can be independently combined. All methods described herein can be performed in a suitable order, unless otherwise specified herein or clearly contradictory to the context. The use of any and all examples, or exemplary language (e.g., "such as") is only to better illustrate the present invention, rather than to limit the scope of the present invention, unless otherwise stated. Any language in the specification should not be interpreted as indicating that any unclaimed element is essential to the practice of the present invention used herein.
[0210] Although the present invention has been described with reference to exemplary embodiments, it will be appreciated by those skilled in the art that various changes may be made and elements thereof may be replaced with equivalents without departing from the scope of the present invention. In addition, many modifications may be made to adapt specific situations or materials to the teachings of the present invention without departing from the basic scope of the present invention. Therefore, the present invention is not intended to be limited to the specific embodiments disclosed as the expected best mode for implementing the present invention, but the present invention will include all embodiments falling within the scope of the appended claims. The present invention includes any combination of the above elements in all possible variations, unless otherwise noted herein or clearly contradictory to the context.
Claims
1. A method for purifying a silk fibroin preparation, comprising: preparing a silk fibroin aqueous solution having a concentration greater than or equal to 5% w / v silk fibroin from the silk fibroin preparation, wherein the silk fibroin preparation comprises a chaotropic salt; and exchanging the chaotropic salt from a silk fibroin solution at a pH below the isoelectric point of the silk fibroin, wherein the pH is between 2 and 5, replacing the chaotropic salt with a buffer containing 10 to 300 mM of a second salt, or The invention relates to a combination of the above-mentioned two kinds of silk fibroin to prepare purified silk fibroin.
2. The method of claim 1, wherein exchanging salt ions comprises continuous diafiltration by tangential flow filtration (TFF), dialysis, or a combination thereof.
3. The method of claim 1, wherein the silk fibroin preparation is prepared by a process comprising dissolving degummed silk fibroin fibers in 5M to 13M LiBr, and wherein the purified silk fibroin preparation comprises 10 to 600 ppm lithium / mg silk.
4. The method of claim 3, wherein the purified silk fibroin preparation comprises 10 to 600 ppm bromine per mass of silk fibroin.
5. The method according to claim 3, wherein the exchange of salt ions from the silk fibroin aqueous solution is carried out by continuous diafiltration using tangential flow filtration (TFF) with a molecular weight cutoff membrane of 5 kDa to 10 kDa, the process comprising: A retentate with a reduced pH is provided and filtered for at least three diafiltration volumes using water instead of feed, wherein the retentate with a reduced pH is a retentate comprising the silk fibroin and having a pH of 2 to 5.
6. The method according to claim 5, wherein prior to providing the reduced pH retentate, the method comprises filtering at least 3 diafiltration volumes, preferably at least 5 diafiltration volumes, with water replacing feed.
7. The method of claim 3 or claim 4, wherein the exchange of salt ions from the aqueous silk fibroin solution is performed by dialysis, wherein the pH of the purified silk solution is 2-5, and wherein the pH is maintained at 2-5 during at least a portion of the dialysis process.
8. The method according to claim 3 or claim 4, wherein the exchange of salt ions from the silk fibroin aqueous solution is performed by continuous diafiltration using tangential flow filtration (TFF) with a molecular weight cutoff membrane of 5 kDa to 10 kDa, the process comprising: Filtration was performed with at least three diafiltration volumes of saline solution replacement feed containing 10 to 300 mM salt.
9. The method according to claim 8, wherein prior to providing the saline solution replacement feed, the method comprises filtering at least 3 diafiltration volumes, preferably at least 5 diafiltration volumes with water replacement feed.
10. The method of claim 8 or 9, wherein the brine alternative feed comprises a Mg salt, a Ca salt, a K salt or a Na salt.
11. The method according to claim 3 or claim 4, wherein exchanging salt ions from the aqueous silk fibroin solution is performed by dialysis in a buffer containing 10 to 300 mM monovalent or divalent salt.
12. The method of claim 1, further comprising adjusting the pH value of the purified silk fibroin preparation to a pH of 7-9, preferably 8.5-9.
13. The method of claim 1, wherein the silk fibroin preparation is prepared by a process comprising dissolving degummed silk fibers using a mixture of calcium chloride, ethanol, and water in a molar ratio of 1:2:8 at 50°C to 100°C for 1 hour to overnight.
14. The method of claim 13, wherein exchanging salt ions comprises continuous diafiltration by tangential flow filtration (TFF), dialysis, or a combination thereof.
15. The method according to claim 13, wherein the exchange of salt ions from the silk fibroin aqueous solution is performed by tangential flow filtration (TFF) using a 5 kDa to 10 kDa molecular weight cutoff membrane, the process comprising: A retentate with a reduced pH is provided and filtered for at least three diafiltration volumes using water instead of feed, wherein the retentate with a reduced pH is a retentate comprising the silk fibroin and having a pH of 2 to 5.
16. The method of claim 15, wherein exchanging salt ions from the aqueous silk fibroin solution is performed by dialysis in a buffer having a pH of 2-5, wherein the pH is maintained at 2-5 during at least a portion of the dialysis process.
17. The method according to claim 15, wherein the exchange of salt ions from the silk fibroin aqueous solution is performed by continuous diafiltration using tangential flow filtration (TFF) with a molecular weight cutoff membrane of 5 kDa to 10 kDa, the process comprising: The filtration is performed with at least three diafiltration volumes of a saline replacement feed comprising 10 to 300 mM of a monovalent or divalent salt.
18. The method according to claim 15, wherein exchanging salt ions from the aqueous silk fibroin solution is performed by dialysis in a buffer containing 10 to 300 mM salt.
19. The method according to any of the preceding claims, wherein the silk fibroin preparation is prepared by degumming silk threads in 0.05 to 1 M sodium carbonate at a temperature of about 60°C to about 90°C for a time period of greater than 60 minutes to about 480 minutes to provide degummed silk fibers having a sericin concentration of 0-0.5 wt%.
Citation Information
Patent Citations
Stable silk protein fragment compositions
US9517191B2
Silk-based products, formulations, and methods of use
WO2020247594A1